Modular and spatially explicit: A novel approach to system dynamics. (August 2017) - Wingo, Patrick; Brookes, Allen; Bolte, John
Abstract: The Open Modeling Environment (OME) is an open-source System Dynamics (SD) simulation engine which has been created as a joint project between Oregon State University and the US Environmental Protection Agency. It is designed around a modular implementation, and provides a standardized interface for interacting with spatially explicit data while still supporting the standard SD model components. OME can be run as a standalone simulation or as a plugin to a larger simulation framework, and is capable of importing Models from several SD model formats, including Simile model files, Vensim model files, and the XMILE interchange format. While it has been released, OME is still under development, and a number of potential future improvements are discussed. To help illustrate the utility of OME, an example model design process is provided as an Appendix. Highlights: System Dynamics engine with a uniform interface for spatially explicit data. Support for importing Simile, Vensim, and XMILE models. Modular design; capable of running standalone, or as a plugin. Ongoing open source development project.